Internal combustion engine fundamentals - Heywood, John B. (McGraw-Hill Education, 2018)
The long-awaited revision of the most respected resource on Internal Combustion Engines --covering the basics through advanced operation of spark-ignition and diesel engines. Written by one of the most recognized and highly regarded names in internal combustion engines this trusted educational resource and professional reference covers the key physical and chemical processes that govern internal combustion engine operation and design. Internal Combustion Engine Fundamentals, Second Edition, has been thoroughly revised to cover recent advances, including performance enhancement, efficiency improvements, and emission reduction technologies. Highly illustrated and cross referenced, the book includes discussions of these engines' environmental impacts and requirements. You will get complete explanations of spark-ignition and compression-ignition (diesel) engine operating characteristics as well as of engine flow and combustion phenomena and fuel requirements.